2021
DOI: 10.1016/j.omto.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

PTOV1 promotes cisplatin-induced chemotherapy resistance by activating the nuclear factor kappa B pathway in ovarian cancer

Abstract: Chemotherapy resistance is a bottleneck for ovarian cancer treatment; therefore, revealing its regulatory mechanism is critical. In the present study, we found that prostate tumor overexpressed-1 (PTOV1) was upregulated significantly in ovarian cancer cells and tissues. Patients with high PTOV1 levels had a poor outcome. In addition, PTOV1 overexpression increased CDDP (cisplatin) resistance, while PTOV1 knockdown inhibited CDDP resistance, as determined using cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…As reported, RPS3 interacts with the p65 subunit of nuclear factor kappa B (NF-κB) through its K homology domain, which results in NF-κB-induced transcriptional activation (38)(39)(40). NF-κB adjusts the expression of genes (PTOV1, c-Myb, TRIM52) (41)(42)(43) related to numerous processes that play a pivotal role in the development and progression of cancer, such as proliferation, migration and apoptosis (44). Many ndings have indicated that NF-κB pathway activation promotes ovarian cancer chemotherapy resistance (41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, RPS3 interacts with the p65 subunit of nuclear factor kappa B (NF-κB) through its K homology domain, which results in NF-κB-induced transcriptional activation (38)(39)(40). NF-κB adjusts the expression of genes (PTOV1, c-Myb, TRIM52) (41)(42)(43) related to numerous processes that play a pivotal role in the development and progression of cancer, such as proliferation, migration and apoptosis (44). Many ndings have indicated that NF-κB pathway activation promotes ovarian cancer chemotherapy resistance (41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB adjusts the expression of genes (PTOV1, c-Myb, TRIM52) (41)(42)(43) related to numerous processes that play a pivotal role in the development and progression of cancer, such as proliferation, migration and apoptosis (44). Many ndings have indicated that NF-κB pathway activation promotes ovarian cancer chemotherapy resistance (41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, other studies show that PTOV1 promotes prostate cancer invasion and growth by counteracting Notch pathway signaling and promoting the translation of JUN (encoding C-Jun) [8]. Moreover, more and more studies showed that PTOV1 as a prognostic factor for patients with many cancers such as ovarian cancer, nonsmall cell lung cancer, urothelial carcinoma and other cancer [9][10][11][12]. And also, PTOV1 might be a target for inhibition of chemotherapy resistance [9,10,13].…”
Section: Introductionmentioning
confidence: 99%
“… 25 NF‐κB expression is strictly regulated in normal cells, but it is generally overexpressed in many cancer cells. 26 Upregulation of NF‐κB has been observed in several types of cancer, including hepatocellular carcinogenesis, 27 , 28 colon cancer, 29 breast cancer, 30 ovarian cancer 31 and glioma cancer. 32 Multiple number of NFKB1 gene SNPs were investigated in the implication of cancer.…”
Section: Introductionmentioning
confidence: 99%